Electrical conductivity and morphological observation of hybrid filler : Silver-graphene oxide nanocomposites for wearable antenna - Al Gburi, Ahmed Jamal Abdullah; Ismail, Mohd Muzafar; Mohammed, Naba Jasim; Buragohain, Akash; Alhassoon, Khaled (Elsevier, 2024)
Copper was formerly used for the antenna conductive patch, which was expensive, subject to multipath fading, bulky, ecologically sensitive, and difficult to manufacture. The miraculous nanotechnology of graphene has made it a feasible contender to replace copper due to its extraordinary electrical conductivity and greater strength compared to metal, all while being adaptable and flexible. As a consequence, graphene is utilized in this study to create conductive silver nanocomposites. The electrical conductivity of pressed pellets of the silver-graphene (Ag/GO) sample is measured using the four-point probe method, resulting in an electrical conductivity value of approximately 21.386 S/cm. The proposed wearable antenna is designed, measured, and fabricated, consisting of a circular patch embedded with four slots to enhance the impedance bandwidth, resonating at 2.45 GHz. Besides, the wearable antenna has achieved a high gain of 11.78 dBi and a return loss of more than − 20 dB. In consideration of health and safety concerns in wearable devices, the specific absorption rate (SAR) is evaluated. The SAR is determined to be 0.9 W/kg per 10 g of tissue for an input power of 0.5 W, confirming the safety of the proposed graphene wearable antenna for use in wearable devices. These findings suggest promising prospects for the utilization of Ag/GO nanocomposites as a conductive patch for wearable antennas in wireless communication.